2015
DOI: 10.1002/jib.203
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Chinese rice wines of different geographical origins by UV-vis spectroscopy and chemometrics

Abstract: Discrimination of Chinese rice wines from four geographical origins ('Zhejiang', 'Jiangsu', 'Shanghai' and "Fujian") in China was investigated according to their UV-vis spectra. The UV-vis absorption spectra of 112 samples in the wavelength range of 190-800 nm were collected. Then the absorption data was subjected to principal component analysis to reveal differences between samples and the potential possibility of using multivariate methods to distinguish differences. Classification models were developed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…PCA uses the mathematical dimension reduction method to eliminate the correlation between variables . Several independent variables are achieved to replace the original variables on the basis of reflecting the information as much as possible.…”
Section: Methodsmentioning
confidence: 99%
“…PCA uses the mathematical dimension reduction method to eliminate the correlation between variables . Several independent variables are achieved to replace the original variables on the basis of reflecting the information as much as possible.…”
Section: Methodsmentioning
confidence: 99%
“…(2004) reported that applying 2D NMR in conjunction with high‐resolution diffusion‐ordered spectroscopy (HR DOSY) could further extend characterization in port wine. UV–vis and IR spectroscopy have also attracted interest as potential methods, with direct UV–Vis, near‐infrared (NIR), and mid‐infrared spectroscopy (MIR) being able to differentiate between samples of beer (Ghasemi‐Varnamkhasti & Forina, 2014), rice wine (Shen et al., 2012; Wu et al., 2015), tequila (Contreras et al., 2010), and various whiskies (Wiśniewska et al., 2017); however, the data obtained are qualitative in character, particularly for UV–Vis spectroscopy, and further characterization would require additional technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Although one-dimensional NMR may yield data of limited scope, two-dimensional NMR has been applied successfully for the identification of some compounds in white and red wine (Mazzei, Spaccini, Francesca, Moschetti, & Piccolo, 2013;Papotti et al, 2013), and Nilsson et al (2004) reported that applying 2D NMR in conjunction with high-resolution diffusion-ordered spectroscopy (HR DOSY) could further extend characterization in port wine. UV-vis and IR spectroscopy have also attracted interest as potential methods, with direct UV-Vis, near-infrared (NIR), and mid-infrared spectroscopy (MIR) being able to differentiate between samples of beer (Ghasemi-Varnamkhasti & Forina, 2014), rice wine (Shen et al, 2012;Wu et al, 2015), tequila (Contreras et al, 2010), and various whiskies (Wiśniewska et al, 2017); however, the data obtained are qualitative in character, particularly for UV-Vis spectroscopy, and further characterization would require additional technologies. Direct analysis with Fourier transform ion cyclotron resonance mass spectroscopy (FTICR-MS) has been applied toward wine and whisky, and it has been shown to allow accurate determination of the main ions in samples, relating to major chemical constituents (Garcia et al, 2013;Kew, Goodall, Clarke, & Uhrín, 2017;Roullier-Gall et al, 2015) .…”
Section: Application Of Nta For Analysis Of Alcohol Contaminantsmentioning
confidence: 99%
“…There is an urgent need for suitable analytical techniques for increasing the understanding of the flavor composition of liquor and the changes associated with fake liquor (Jia et al, 2014;Li et al, 2014;Sun et al, 2015;Wu et al, 2015). In previous studies, most analytical methods were based on flavor components, stable isotopes, and trace metal elements using different spectroscopic and chromatographic methods to characterize varieties and perform geographical origin discrimination of alcoholic beverages, including gas chromatography (GC) (Xu et al, 2017), gas chromatography-mass spectrometry (GC-MS) (Welke et al, 2013;Ziókowska et al, 2016), gas chromatography-olfactometry (GC-O) (Fan & Qian, 2006;Li et al, 2019), near-infrared spectroscopy (NIR) (Fei et al, 2012), NMR spectroscopy (Kuballa et al, 2018;Monakhova et al, 2014), UV-vis spectra (Wu et al, 2015), isotope ratio mass spectrometry (IRMS) (Jiang et al, 2015), inductively coupled plasma-mass spectrometry (ICP-MS) (Geana et al, 2013), mass spectrometry-electronic nose (MS-EN) (Cynkar et al, 2010), colorimetric artificial nose (Qin et al, 2012), and other methods. Overall, modern analytical techniques are more persuasive in revealing the microscopic composition of liquor than sensory taste.…”
Section: Introductionmentioning
confidence: 99%